1991
DOI: 10.1007/bf03160997
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic fate of [3H-methyl]choline in cultured human neuroblastoma cell lines, LA-N-1 and LA-N-2

Abstract: The conversion of choline in cultures of the human neuroblastoma cell lines, LA-N-1 and LA-N-2 cells, was investigated in order to identify potential precursors in acetylcholine (AcCho) synthesis. LA-N-1, a catecholaminergic and LA-N-2, a cholinergic, cell line were incubated with [ 3 H-methyl]choline (Cho) for varying periods of time up to 72 h. The radioactivity present in lipids and watersoluble metabolites increased linearly up to 24 h in both cell lines. Approximately 20% of the radioactivity associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous reports demonstrated that LA-N-2 cells propagated in the presence of lop5 M retinoic acid (RA) underwent morphological differentiation and there were accompanying changes in certain enzymatic activities (Singh et al, 1990). Therefore, it seemed reasonable to determine whether TPA exerted a similar influence on the labeling with Table I, whic;.. shows that the retinoic acid-grown cells as compared to control cells 1) were unresponsive to TPA with respect to lipid and protein labeling and 2) had a reduced capacity to incorporate either labeled Ea or labeled Ser into lipids and proteins but increased incorporation of labeled Cho into lipids.…”
Section: Retinoic Acid Grown Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports demonstrated that LA-N-2 cells propagated in the presence of lop5 M retinoic acid (RA) underwent morphological differentiation and there were accompanying changes in certain enzymatic activities (Singh et al, 1990). Therefore, it seemed reasonable to determine whether TPA exerted a similar influence on the labeling with Table I, whic;.. shows that the retinoic acid-grown cells as compared to control cells 1) were unresponsive to TPA with respect to lipid and protein labeling and 2) had a reduced capacity to incorporate either labeled Ea or labeled Ser into lipids and proteins but increased incorporation of labeled Cho into lipids.…”
Section: Retinoic Acid Grown Cellsmentioning
confidence: 99%
“…The human neuroblastoma cell line, LA-N-2 (passage Sl), was obtained from Dr. Robert Seeger, University of California, Los Angeles. The maintenance and growth conditions for this cell line were as described by Singh et al (1990). At 8 days in culture (DIV) the LA-N-2 cell cultures containing approximately 1 mg protein were washed once with serum-free L-15 medium and replaced with 5 ml of serum-free medium containing either ['4C]Cho (1.2 pCi/ ml), [14C]Ea (1.5 pCi/ml), or [14C]Ser (1 pCi/ml) along with either 100 nM TPA in dimethylsulfoxide (DMSO) or DMSO alone (0.1% final concentration).…”
Section: Cell Culture and Labeling Protocolsmentioning
confidence: 99%
See 1 more Smart Citation